Comparative Analysis of AHP and SMART Methods in Lecturer Performance Assessment for Providing Incentives to STIKOM Cipta Karya Informatics - Rasiban; Rizki Ananda Pratama (Yayasan Sinergi Multidimensi Kreatif, 2024)
The quality of human resources is one of the supporting factors to increase the productivity of an agency's performance, highly competent human resources can support the level of performance, with a performance assessment, it will be known the achievements achieved by each employee in Higher Education Rewards or assessments in the form of incentives are a form of gratitude to lecturers for the dedication and performance that lecturers have given to universities. In this study, two methods were used in decision-making to provide incentives based on performance assessment. AHP (Analytical Hierarchy Process) method and SMART method (Simple Multi Attribute Rating Technique) with a study on Lecturers at STIKOM Cipta Karya Informatika. At the analysis stage using the two methods, the results were obtained that the performance assessment using the AHP method was only 3 lecturers out of 10 lecturers who were entitled to incentives with an assessment decision of 21.00 to 24.00 were entitled to incentives and an assessment of 0.00 to 20.00 did not get incentives. Analysis using the SMART method found that 4 lecturers out of 10 lecturers who were entitled to incentives with an assessment decision of 1.5 to 2.4 were entitled to incentives and 0.00 to 1.4 did not get incentives. From the results of data analysis in this study, it was also obtained that the assessment of incentive decisions is more appropriate using the SMART method than using the AHP method.